The Impact Of Workload, Leadership, And Non-Physical Work Envirement On Turnover Intention Among Expedition Couriers. - Lilik Yulistya Dewi; Irwan Cahyadi; Febria Nurmelia Marlina (Business Management, 2026)
This study aims to determine the effect of workload, leadership, and non-physical work environment on turnover intention among couriers, both partially and simultaneously. The type of research used in this study is quantitative with the application of SPSS Version 25. The research sample consisted of 37 employees in the courier section of an expedition company. The data collection technique used in this study was a questionnaire. The results of this study indicate that workload does not affect turnover intention, leadership affects turnover intention, and the non-physical work environment affects turnover intention. The variables of workload, leadership, and non-physical work environment have contributed 71.4% to turnover intention, although 28.6% of the influence comes from other factors not included in this study.